Effects of Lung Expansion Therapy on Lung Function in Patients with Prolonged Mechanical Ventilation. (29th March 2016) - Chen, Yen-Huey; Yeh, Ming-Chu; Hu, Han-Chung; Lee, Chung-Shu; Li, Li-Fu; Chen, Ning-Hung; Huang, Chung-Chi; Kao, Kuo-Chin
Abstract : Common complications in PMV include changes in the airway clearance mechanism, pulmonary function, and respiratory muscle strength, as well as chest radiological changes such as atelectasis. Lung expansion therapy which includes IPPB and PEEP prevents and treats pulmonary atelectasis and improves lung compliance. Our study presented that patients with PMV have improvements in lung volume and oxygenation after receiving IPPB therapy. The combination of IPPB and PEEP therapy also results in increase in respiratory muscle strength. The application of IPPB facilitates the homogeneous gas distribution in the lung and results in recruitment of collapsed alveoli. PEEP therapy may reduce risk of respiratory muscle fatigue by preventing premature airway collapse during expiration. The physiologic effects of IPPB and PEEP may result in enhancement of pulmonary function and thus increase the possibility of successful weaning from mechanical ventilator during weaning process. For patients with PMV who were under the risk of atelectasis, the application of IPPB may be considered as a supplement therapy for the enhancement of weaning outcome during their stay in the hospital.